PENGARUH KONSENTRASI EKSTRAK BAWANG MERAH DAN BAHAN SETEK TERHADAP PERTUMBUHAN TANAMAN MELATI (Jasminum sambac L.) KULTIVAR BANDAR ARUM - Riana, Ade Yuni; Eviyati, R; Dukat, Dukat (Agroswagati : Jurnal Agronomi, 2025)
This study aims to determine the effect of the combined concentration of shallot extract and cutting material on growth of jasmine (Jasminum sambac. L). This research was carried out in the village of Cilengkrang Girang, Pasaleman District, Cirebon Regency. In April to July 2021. The method in this research is the experimental method with non factorial completely randomized design. The treatment consisted of combination of cutting materials and shallot extract concentration. (A)= top stam cutting + concentration of 50%, (B) = middle stam cutting + concentration of 50%, (C)= bottom stam cutting + concentration of 50%, (D)= top stam cutting + concentration of 75%, (E)= middle stam cutting + concentration of 75%, (F)= bottom stam cutting + concentration of 75%, (G)= top stam cutting + concentration of 100%, (H)= middle stam cutting + concentration of 100%, (I)= bottom stam cutting + concentration of 100%. The treatment combination consisted of 9 and all were repeated 3 times, and there are 27 experimental unit treatments. The result show that the concentration of shallot extract and cutting material had no significant effect on growth of jasmine (Jasminum sambac. L) cultivar Bandar Arum.